Glutamate Transporter GLT-1 Is Transiently Localized on Growing Axons of the Mouse Spinal Cord before Establishing Astrocytic Expression - Yamada, Keiko (J Neurosci, 1998)
The glutamate transporter GLT-1 is expressed in astrocytes of the mature brain and spinal cord. In the present study, we examined its expression in the developing mouse spinal cord. By in situ hybridization, (35)S-labeled antisense oligonucleotide probes for GLT-1 mRNA consistently labeled the mantle zone/gray matter from embryonic day 11 through the adult stage. However, immunohistochemistry with a specific antibody visualized distinct regional and cellular localizations during the time between the fetal and postnatal stages. At fetal stages, GLT-1 immunoreactivity predominated in the marginal zone/white matter, observed as tiny puncta in cross-sections and as thin fibers in longitudinal sections. The GLT-1-immunopositive structures were also labeled for neuron-specific enolase, a glycolytic enzyme specific to postmitotic neurons and endocrine cells. By electron microscopy, GLT-1 immunoreactivity was detected in axons forming frequent enlargements and was focally localized on a small portion of the axolemma, particularly that facing adjacent axons. At early postnatal stages, GLT-1 disappeared from axons in white matter tracts and, instead, appeared in astrocytic processes surrounding various neuronal elements in the gray matter. Therefore, before switching to astrocytic expression, GLT-1 is transiently expressed in neurons and localized in differentiating axons. Together with our previous finding on the localization of glutamate transporter GLAST in radial glial fibers, GLT-1 and GLAST are thus localized during development on distinct directional cellular elements along which young neurons elongate their axons or move their cell bodies, respectively.